Wrongful behaviours among manufacturing employees in Malaysia: An exploratory study - Mohd Shamsudin, Faridahwati; Subramaniam, Chandrakantan; Ibrahim, Hadziroh (Social Science Electronic Publishing, Inc, 2011)
Wrongful behaviour is an important subject that needs to be seriously understood as it represents a reality of work life amongst employees in organizations.Furthermore, managers and practitioners should be concerned about this phenomenon since it may bring harmful effects to the organization in the long run if it is not effectively managed.To do so, managers need to understand the nature of it.This paper reports some findings of a survey conducted among 324 manufacturing employees in some parts of Malaysia.Three different forms of wrongful behaviour have been identified i.e. irresponsible behaviour, nonproductive behaviour and loitering behaviour.The survey generally found that manufacturing employees tend to engage in organizational deviance/wrongful behaviour.Discussion on the findings, their implications to practice and research, and limitations of the studies are also highlighted in this paper.